A synthetic methylotroph achieves accelerated cell growth by alleviating transcription-replication conflicts - Xin Meng; Guipeng Hu; Xiaomin Li; Cong Gao; Wei Song; Wanqing Wei; Jing Wu; Liming Liu (Nature Communications)
Abstract Microbial utilization of methanol for valorization is an effective way to advance green bio-manufacturing technology. Although synthetic methylotrophs have been developed, strategies to enhance their cell growth rate and internal regulatory mechanism remain underexplored. In this study, we design a synthetic methanol assimilation (SMA) pathway containing only six enzymes linked to central carbon metabolism, which does not require energy and carbon emissions. Through rational design and laboratory evolution, E. coli harboring with the SMA pathway is converted into a synthetic methylotroph. By self-adjusting the expression of TOPAI (topoisomerase I inhibitor) to alleviate transcriptional-replication conflicts (TRCs), the doubling time of methylotrophic E. coli is reduced to 4.5 h, approaching that of natural methylotrophs. This work has the potential to overcome the growth limitation of C1-assimilating microbes and advance the development of a circular carbon economy.